Hydrodynamics at the Navier-Stokes level applied to fast, transient, supersonic granular flows - Almazan Torres, Lidia; Salueña, Clara; Garzó, Vicente; Carrillo, José A.; Pöschel, Thorsten (28th International Symposium on Rarefied Gas Dynamics 2012, RGD 2012, 2012)
We perform two-dimensional hydrodynamic simulations on a paradigmatic problem of granular dynamics, the Faraday instability, using two different approximations to the Navier-Stokes granular equations: the constitutive equations and kinetic coefficients derived from the assumption of vanishing inelasticity (Jenkins-Richman approach) obtained by solving the Enskog equation disks by means of Grad's method, and the ones obtained by solving the Enskog equation with the Chapman-Enskog method (Garzó-Dufty-Lutsko approach). The comparison reveals important qualitative and quantitative differences with respect to the hydrodynamic fields obtained by averaging results from particle simulations of the same system. © 2012 American Institute of Physic
Keywords: Faraday instability; hydrodynamic simulations; molecular dynamics; Rapid granular flows